2017
DOI: 10.1007/s10068-017-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kluyveromyces marxianus on proteins, peptides, and amino acids in Lactobacillus-fermented milk

Abstract: With increasing application of yeast in fermented milk, in order to study the effect of yeast on milk protein during the fermentation process, the effects of the presence of in milk fermented by and were investigated. After fermentation, the amino acid, protein, and peptide contents were analyzed by ultra-performance liquid chromatography, two-dimensional gel electrophoresis, and liquid chromatography-mass spectrometry, respectively. After the addition of for fermentation, 25 protein spots changed significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…This was in consistent with Chaves-López et al [25], who reported that co-culturing with yeasts was able to promote the multiplication of LAB. This phenomenon might be attributed to the release of amino acids and vitamins through the metabolism of yeast [26], which might provide more nutrients for the growth of LAB.…”
Section: The Growth and Acidification Performance Of Labmentioning
confidence: 99%
“…This was in consistent with Chaves-López et al [25], who reported that co-culturing with yeasts was able to promote the multiplication of LAB. This phenomenon might be attributed to the release of amino acids and vitamins through the metabolism of yeast [26], which might provide more nutrients for the growth of LAB.…”
Section: The Growth and Acidification Performance Of Labmentioning
confidence: 99%
“…At the fungal level, Candida was the absolutely advantageous genus in both two types of dairy products, while Aspergillus and Kluyveromyces were the subsequent dominant genera in RM and SK samples, which differed with others study [46]. The Kluyveromyces marxianus used in fermented food had the characteristics of weak alcohol and good aroma production, and could increase the content of free fatty acids and flavor substances in yogurt [47, 48]. Maybe, that’s why the flavor of SK is different from the other yogurts.…”
Section: Discussionmentioning
confidence: 97%
“…This is in agreement with the work of Chaves-López et al (2014), who reported that co-culturing with yeasts was able to promote the multiplication of LAB. This phenomenon might be attributed to the release of amino acids and vitamins through the metabolism of yeasts (Zhang et al, 2017), which might provide more nutrients for the growth of LAB. Unlike contaminating microorganisms, the abundance and maintenance of yeasts, molds and lactic acid bacteria in nonnonkoumou would surely also be linked on one hand to their capacity to tolerate high concentrations of organic acids and therefore to low pH, and on the other part, to their ability to use the substrates present in the fermentation medium for their development.…”
Section: Discussionmentioning
confidence: 99%